Habitual Exercise, Air Pollution, and Pneumonia Mortality: A Longitudinal Cohort Study of Approximately 0.4 Million Adults. Issue 10 (1st July 2022) - Guo, Cui; Yu, Tsung; Lin, Changqing; Chang, Ly-Yun; Bo, Yacong; Wong, Martin C S; Tam, Tony; Lau, Alexis K H; Lao, Xiang Qian
Abstract: In this study, we aimed to examine the combined associations of particulate matter with an aerodynamic diameter less than or equal to 2.5 μm (PM2.5 ) and habitual exercise with pneumonia mortality. We included 384, 130 persons aged ≥18 years from Taiwan, Republic of China, during 2001–2016. We followed participants until May 31, 2019, to obtain information on vital status. A time-dependent Cox regression model was used for statistical analysis. We found that risks of pneumonia mortality were reduced by 55% (hazard ratio (HR) = 0.45, 95% confidence interval (CI): 0.36, 0.55) and 36% (HR = 0.64, 95% CI: 0.52, 0.80) in participants who engaged in high and moderate levels of exercise, respectively, as compared with inactive persons. By contrast, each 10-μg/m 3 increase in chronic PM2.5 exposure was associated with a 30% (HR = 1.30, 95% CI: 1.17, 1.45) higher risk of pneumonia mortality. Risk of pneumonia death was 72% lower (HR = 0.28, 95% CI: 0.20, 0.41) for persons with a high exercise level and a low PM2.5 level. Lower risk of pneumonia mortality was associated with both higher exercise and lower PM2.5 air pollution levels. For adults exposed to different levels of PM2.5, exercise benefits remained. Our findings suggest that engaging in exercise is a safe and effective strategy for alleviating the burden of pneumonia mortality, even for people who reside in a moderately polluted area.